Wheat Research Station, Wellington – An Overview - Kumar, Jagdish; Sivasamy, M; Jayaprakash, P; Vikas, V K (Journal of Cereal Research, 2011)
Rust pathology work is undertaken here very much parallel to other wheat rust laboratories in the country for supplementary/confirmatory conclusions. Moreso, this station is an excellent standby wheat rust laboratory in the country.